Cost-effectiveness analysis of a sealing hemostat patch (HEMOPATCH) vs standard of care in cardiac surgery. (4th March 2018) - Ikeme, Shelly; Weltert, Luca; Lewis, Kevin M.; Bothma, Gerhard; Cianciulli, Daniela; Pay, Nicole; Epstein, Josh; Kuntze, Erik
Abstract: Background: A recent randomized controlled trial showed that patients undergoing ascending aorta surgery treated with HEMOPATCH to control bleeding had a significantly better hemostasis success rate than with dry or wet gauze compression or similar standard of care (SOC). Objective: To compare the cost-effectiveness using two different agents for hemostasis (HEMOPATCH vs dry or wet gauze compression or similar SOC) in cardiac surgery from the European hospital perspective. Methods: A literature-based cost-effectiveness model estimating average cost per successful hemostasis event was developed based on the hemostasis efficacy difference (HEMOPATCH = 97.6%, SOC = 65.8%, p < .001). Additional clinically significant end-points studied in the trial (blood transfusions and surgical revisions) were also analyzed. It was assumed that each surgery utilized two units of HEMOPATCH (dimensions of 4.5 × 9 cm) and two units of SOC. Product acquisition costs for HEMOPATCH and SOC were included along with outcome-related costs derived from the literature and inflation-adjusted to 2017 EUR and GBP. Results are presented for an average hospital with an annual case load of 574 cardiac surgeries. One-way and probabilistic sensitivity analyses were performed. Results: Considering only product acquisition cost, HEMOPATCH had an incremental cost-effectiveness ratio (ICER) of €1, 659, €1, 519, €1, 623, and £1, 725 per hemostasis success when compared to SOC for Italy, Spain, France, and the UK, respectively. However, when considering the cost and potential difference in the frequency of transfusions and revisions compared to SOC, the use of HEMOPATCH was associated with an annual reduction of six revisions and 60 transfusions, improving the ICER to €1, 440, €1, 222, €1, 461, and £1, 592, respectively. Sensitivity analysis demonstrated model robustness. Conclusions: This analysis supports the use of HEMOPATCH over SOC in cardiac surgery in European hospitals to improve hemostasis success rates and potential cost offsets from reduced transfusions, complications, and surgical revisions.